Inorganic salt templated porous TiO2 photoelectrode for solid-state dye-sensitized solar cells. Issue 1 (21st December 2015) - Li, Hao; Li, Shichao; Zhang, Ye; Yan, Feng
Abstract : Salt template induced TiO2 photoelectrodes with channels (or pores) were applied to improve the photoelectric conversion efficiency of solid-state dye-sensitized solar cells. Abstract : TiO2 photoelectrodes with channels (or pores) are prepared by using an inorganic salt (NaHCO3 ) as a template. NaHCO3 doped TiO2 slurries deposited on a compacted TiO2 film are heated at 150 °C, which releases CO2 gas and water vapour, thus forming channels (or pores) inside a TiO2 light-scattering photoelectrode. These channels (pores) improve the penetration degree of solid-state electrolytes into the TiO2 photoelectrode and enhance the photovoltaic efficiency of resulting DSSCs (dye sensitized solar cells). With a channel (pore) size of ∼500 nm diameter, an ionic liquid plastic crystal, 5-azoniaspiro[4.4]nonane bis(trifluoromethanesulfonyl)imide (N44 TFSI), shows power conversion efficiencies of 6.1% and 5.4% under 1.5 solar spectrum illuminations at 50 and 100 mW cm −2, respectively.